Changes in Vestibulo-Ocular Reflex Gain After Surgical Plugging of Superior Semicircular Canal Dehiscence - Lee, Sang-Yeon; Bae, Yun Jung; Kim, Minju; Song, Jae-Jin; Choi, Byung Yoon; Koo, Ja-Won (Frontiers in Neurology, 2020)
Superior semicircular canal dehiscence (SCD), which is characterized by a “third mobile window” in the inner ear, causes various vestibular and auditory symptoms and signs. Surgical plugging of the superior semicircular canal (SC) can eliminate the symptoms associated with increased perilymph mobility due to the presence of the third window. However, the natural course of vestibular function after surgical plugging remains unknown. Therefore, we explored longitudinal vestibular function after surgery in 11 subjects with SCD who underwent SC plugging using the middle cranial fossa approach. Changes in vestibulo-ocular reflex (VOR) gain in all planes were measured over 1 year with the video head impulse test. We also evaluated surgical outcomes, including changes in symptoms, audiometric results, and electrophysiological tests, to assess whether plugging eliminated third mobile window effects. The mean VOR gain for the plugged SC decreased from 0.81 ± 0.05 before surgery to 0.65 ± 0.08 on examinations performed within 1 week after surgery but normalized thereafter. Four of seven subjects who were able to perform both VOR tests before surgery and immediately after surgery had pathologic values (SC VOR gain < 0.70). Conversely, the mean VOR gain in the other canals remained unchanged over 1 year. The majority of symptoms and signs were absent or markedly decreased at the last follow-up evaluation, and no complications associated with the surgery were reported. Surgical plugging significantly attenuated the air-bone gap, in particular at low frequencies, because of increased bone conduction thresholds and deceased air conduction thresholds. Moreover, surgical plugging significantly increased vestibular-evoked myogenic potential thresholds and decreased the ratio of summating potential to action potential in plugged ears. Postoperative heavily T2-weighted images were available for two subjects and showed complete obliteration of the T2-bright signal intensity in the patent SC lumen in preoperative imaging based on filling defect at the site of plugging. Our results suggest that successful plugging of dehiscent SCs is closely associated with a transient, rather than persistent, disturbance of labyrinthine activity exclusively involved in plugged SCs, which may have clinical implications for timely and individualized vestibular rehabilitation.